The association between neutrophil counts and neutrophil-to-lymphocyte ratio and stress hyperglycemia in patients with acute ischemic stroke according to stroke etiology - Feng, Xianjing; Yu, Fang; Wei, Minping; Luo, Yunfang; Zhao, Tingting; Liu, Zeyu; Huang, Qin; Tu, Ruxin; Li, Jiaxin; Zhang, Boxin; Cheng, Liuyang; Xia, Jian (Frontiers in Endocrinology, 2023)
Abstract Background and purpose: Stress hyperglycemia ratio (SHR), which is used to assess stress hyperglycemia, is associated with the functional outcome of ischemic stroke (IS). IS can induce the inflammatory response. Neutrophil counts and neutrophil-to-lymphocyte ratio (NLR) as good and easily available inflammatory biomarkers, the relationship between neutrophil counts and NLR and SHR were poorly explored in IS. We aimed to systemically and comprehensively explore the correlation between various blood inflammation markers (mainly neutrophil counts and NLR) and SHR. Methods: Data from 487 patients with acute IS(AIS) in Xiangya Hospital were retrospectively reviewed. High/low SHR groups according to the median of SHR (≤1.02 versus >1.02). Binary logistic regression analysis was used to evaluate the correlation between neutrophil counts and NLR and high SHR group. Subgroup analyses were performed in the TOAST classification and functional prognosis. Results: The neutrophil counts and NLR were all clearly associated with SHR levels in different logistic analysis models. In the subgroup analysis of TOAST classification, the higher neutrophil counts and NLR were the independent risk factors for high SHR patients with large-artery atherosclerosis (LAA) (neutrophil: adjusted OR:2.047, 95% CI: 1.355-3.093, P=0.001; NLR: adjusted OR:1.315, 95% CI: 1.129-1.530, P<0.001). The higher neutrophil counts were the independent risk factor for high SHR patients with cardioembolism (CE) (adjusted OR:2.413, 95% CI: 1.081-5.383, P=0.031). ROC analysis showed that neutrophil counts was helpful for differentiating high SHR group with CE and low SHR group with CE (neutrophil: AUC =0.776, P=0.002). However, there were no difference in levels of neutrophil counts and NLR between patients with SVO and without SVO. The higher neutrophil counts and NLR independently associated with high SHR patients with mRS ≤2 at 90 days from symptom onset, (neutrophil: adjusted OR:2.284, 95% CI: 1.525-3.420, P<0.001; NLR: adjusted OR:1.377, 95% CI: 1.164-1.629, P<0.001), but not in patients with mRS >2. Conclusions: This study found that the neutrophil counts and NLR are positively associated with SHR levels in AIS patients. In addition, the correlation between neutrophil counts and NLR and different SHR levels are diverse according to TOAST classification and functional prognosis.